Chinese Compliance to Carbon Emissions Trading Regulations: A Three Mechanism Legal Compliance Approach - Wijaya, I Made Marta (Kertha Patrika; Vol 46 No 1 (2024)DO - 10.24843/KP.2024.v46.i01.p06, 2024)
The Hobbesian mechanism emphasizes the enforcement of sanctions as the primary means to ensure compliance, while the Durkheimian mechanism focuses on the symbolic legitimacy of the law and the importance of morality in law enforcement, and the Habermasian mechanism centers on rational communication and consensus in achieving societal compliance. This research aims to identify the application of these three legal compliance mechanisms (Hobbesian, Durkheimian, and Habermasian) in China regarding the implementation of carbon emissions trading regulations under the Kyoto Protocol 1997 and the Paris Agreement 2015 by the United Nations Framework Convention on Climate Change. The study employs normative legal research methods with legislative and conceptual approaches. The findings reveal regional variations in the implementation of carbon emissions trading regulations in China, with diverse levels of compliance among companies. Although overall compliance is relatively high, challenges in enhancing compliance persist, particularly in regions like Beijing and Tianjin. Factors such as local government policies, imposed sanctions, and administrative capacity play crucial roles in determining compliance levels. Analysis of compliance with carbon emissions trading regulations across different administrative levels in China demonstrates diverse outcomes. At the central level, Chinese government compliance with regulations is driven by moral awareness of climate change, reflecting the Durkheimian mechanism. Meanwhile, regional differences in compliance are attributed to variations in regulations concerning incentives and sanctions, with Tianjin exhibiting low compliance due to lax sanctions (Hobbesian mechanism), while Shanghai and Guangdong show high compliance due to rational consensus between the government and companies (Habermasian mechanism).